PENGARUH MULTI NUTRIENT SAUCE (MNS) DENGAN DOSIS YANG BERBEDA DALAM RANSUM TERHADAP KECERNAAN PROTEIN KASAR DAN SERAT KASAR PADA DOMBA - M Alvin Rifqi Fadilla, Erwanto, Muhtarudin, dan Agung Kusuma Wijaya (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
The purpose of this research was to determine the effect of addition of Multinutrient Sauce (MNS) in the ration on digestibility of crude protein and crude fiber in sheep. This research was conducted in May—July 2019 at the People's Farm of Kebagusan Village, Gedong Tataan District, Pesawaran Regency. The digestibility analysis of crude protein and crude fiber was carried out at the Laboratory of Animal Nutrition and Feed, Animal Husbandry Department, Faculty of Agriculture, University of Lampung. This study used a randomized block design (RBD) based on sheep body weight with six groups and three treatments, namely R0 (ration without MNS); R1 (R0 + MNS 5%); and R2 (R0 + MNS 10%). The data obtained were analyzed using ANOVA at a 5% significance level or 1% significance, and continued with further test using Least Significant Difference Test (LSD) if there is significant results. The results showed that the addition of 10% MNS in the ration had a significant effect (P<0.05) on increasing the digestibility of crude protein and crude fiber in sheep. Keywords: multi nutrient sauce (MNS), digestibility of crude protein, digestibility of crude fiber, sheep.